Sistem Pakar untuk Mendiagnosa Penyakit Syaraf dengan Metode Forward Chaining - Joko Kuswanto; Leni Pebriantika; Sulia Ningsih (STMIK Budi Darma, 2022)
The development of information technology that is developing rapidly, is very helpful in all aspects and even able to process, adopt and think like a human being called an expert system. The expert system that will be built is to diagnose neurological diseases. The method used in this study is forward chaining which is considered simple but easy to understand. With the existence of an expert system, it is hoped that ordinary people can solve complicated problems in this case neurological diseases that can actually only be solved with the help of experts. For experts themselves, the existence of an expert system will also help their activities as a very experienced assistant. From the results of the tests that have been carried out, it shows that the expert system is suitable for use to diagnosea neurological disease